Honey Creek Novel: Dinner on Primrose Hill - Book 3 - Thomas, Jodi (New York, NY : Zebra Books/Kensington Publishing Corp., 2021)
"Benjamin Monroe is pretty sure how his life will play out. Hell continue teaching chemistry in his small college, and spend his free time biking through the valley. Eventually, hell retire to putter around in his garden and greenhouse. His colleague, Virginia Clark, is not one for routines. Shes chatty, spontaneous, and bubbly, and before Benjamin realizes what happened, shes talked him into collaborating on a research project<U+2014 >studying the mating habits of college students. Virginia knows her desire to work with Benjamin is motivated by more than the potential prize money...and hopes he might not be quite as indifferent as he seems to be. Ketch Kincaid, one of Benjamins star students, returned to college after serving in the army. He needs something to get his mind off his recent breakup and collecting research data might do it. And theres another distraction on the horizon<U+2014>a woman who looks like she, too, knows about heartache. Soon enough, their project, zThe Chemistry of Mating," is gaining notoriety. Friends, neighbors, the whole town has become involved. But no matter what the data determines, one conclusion seems inescapable: love follows its own rules"--Provided by publisher.
Keywords: College teachers -- Fiction; Man-woman relationships -- Fiction; Research -- Fiction; Texas -- Fiction; Romance fiction